Promoting Community Health and Fitness: A Collaborative Approach to Mass Aerobic Exercise as a Medium for Fitness Education at FORMASMA 2025 - Rohmana, Via Diah; Puspodari; Lusianti, Septyaning; Shandy, Dwi Kurnia; Handayani, Ruruh Bekti; Sukmana, Asgi; Kodriyah, Nurma Kusnun (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Number of lifestyle-related health problems, including obesity, high blood pressure, and diabetes. To combat these trends, community-oriented recreational sports such as aerobic exercise offer a promising solution to enhance public health outcomes. FORMASMA (Festival Olahraga Masyarakat) 2025 serves as a valuable platform to promote health and wellness through accessible and large-scale community activities. Mass aerobic sessions, in particular, are known to improve heart health, physical coordination, and overall well-being, while also encouraging social engagement. The success of these efforts, however, relies heavily on comprehensive planning, collaboration across sectors, and long-term sustainability. This community service program is envisioned not merely as an isolated event but as part of a broader effort to instill healthy lifestyles into daily routines. By integrating aerobic exercise with health education, this initiative seeks to involve individuals across various age groups youth to seniors in a collective movement towards a healthier, more physically active community.